Visual art education innovative learning and teaching approach in secondary school / Suhaila Mohd Saleh and Muhammad Faiz Sabri - Mohd Saleh, Suhaila; Sabri, Muhammad Faiz (Faculty of Art and Design, 2024)
Learning and teaching in the 21st century have undergone tremendous process due to technological impact on the students and their learning process. The main purpose of this study is to review two academic articles regarding the issue and discussion brought about innovative learning in Visual Art Education subjects in secondary schools in Malaysia. In detail, the articles discussed the uses of technology and gamification methods to enhance the teaching and learning of Visual Art Education, particularly within the secondary school context. Therefore, the articles were chosen based on criteria that were published from 2019 until 2021, and the background of the articles covered the study in Malaysia. Contrary to what has often been assumed, the findings demonstrate that creative and innovative approaches are much more beneficial compared to conventional learning and teaching in school, thus bringing upon research centred in innovative learning around gamification that has emerged as a powerful platform for education making it more fun and effective.